PENYELESAIAN SENGKETA AKIBAT KESALAHAN KURATOR DARI BERKURANGNYA HARTA DEBITUR PAILIT YANG MERUGIKAN PIHAK KREDITUR DALAM KEPAILITAN - M. Taufik Hidayat (Al-Adl : Jurnal Hukum, 2015)
Curator in carrying out their duties based on the principle of fiduciary duty, which means task assigned based on the trust that appoint the curator, the court. Therefore, it's reasonable if the article 72 Bankruptcy Act of 2004 provides that: “curator is responsible for it mistakes or omissions in carrying out managing and/or settlement duties which led to losses against the bankruptcy assets. This trigger so that the curators do their job as well as possible and carefully. In addition, the curators can be sued and must pay restitution if due to their negligence, even more due to fault (deliberate) has caused the parties interested in the bankruptcy assets, affected mainly to the unsecured creditors. Those Losses mainly if  the value of bankruptcy assets were decreased and thus the creditors obtain repayment less than necessary bills received from the sale of bankruptcy assets. This research applied a method of normative juridical approach as it resarch type, so called babecause the research looks at law from a normative aspect. From the results of research conducted, it can be concluded that the legal protection of the curator in the management and settlement bankruptcy assets in the law No. 37 of 2004 (on bankruptcy and postponement of debt payment obligations)   has provided a good legal protection to the curator in carrying out handling tasks and settlement bankruptcy assets. Keywords: curator, mistakes managing of banckruptcy assets and bankruptcy